American oak imports to Britain and Ireland in the 18th and early 19th centuries; The dendrochronological evidence - A. Crone; A. Arnold; R. Bale; M. Bridge; D. Brown; E. Cook; C. Griggs; R. Howard; D. Miles; C. Mills; N. Nayling; C. Tyers; et al. (Dendrochronologia, 2026)

Development and Evaluation of an HPV Vaccine Champion Training: a Strategy to Boost Adolescent Vaccination in Community Health Centers in Florida - Heather N. Owens; Mariana Arevalo; Ashley Whitmer; Lindsay Fuzzell; Carley Geiss; Kea Turner; Katherine Chung-Bridges; Edelise Endemano; Daniel Parras; Shannon M. Christy; Susan T. Vadaparampil (Journal of Cancer Education, 2026)

A decision support tool for determination of stormwater wetland and bioretention system suitability in coastal South Carolina - Dhanuska B. Wijesinghe; Daniel R. Hitchcock; Dara M. Park; David L. White; Anand D. Jayakaran; William Bridges (Ecological Engineering, 2026)

Organic anion transporter 1 (OAT1) is a mechanism for uptake of mercuric-cyanide complexes into proximal tubular cells - Ryan Brownlee; Maria E.A. Galiciolli; Lucy Joshee; Adam M. Kiefer; Caryn S. Seney; Christy C. Bridges (Environmental Toxicology and Pharmacology, 2026)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Social group membership does not facilitate spatial learning of fine-scale resource locations - Angela M. Pitera; Virginia K. Heinen; Benjamin R. Sonnenberg; Lauren M. Benedict; Eli S. Bridge; Vladimir V. Pravosudov (Behavioral Ecology and Sociobiology, 2025)

OS02-09 Skin sensitization potency assessment of fragrance chemicals for quantitative risk assessment – comparing in vivopotency values to the point-of-departure derived with new approach methodologies - A. Natsch; A. Irizar; P. Griem; J. Bridges; H.J. Bender; M. Vey; I. Lee; A.M. Api; P. Kern; I. Kimber (Toxicology Letters, 2025)

Predicting the future distribution of a commercially important clam (Ruditapes philippinarum) in a changing climate - Alexandra S. Johnson; Amelia E.H. Bridges; Antony M. Knights (Estuarine, Coastal and Shelf Science, 2025)

TropiRoot 1.0: Database of tropical root characteristics across environments - Amanda L. Cordeiro; Daniela F. Cusack; Nathaly Guerrero‐Ramírez; Richard J. Norby; Laura Toro; Michelle Y. Wong; S. Joseph Wright; Kristine Grace M. Cabugao; Kelly M. Andersen; Lucia Fuchslueger; Colleen M. Iversen; Fiona Soper; et al. (Ecology, 2025)
Tropical ecosystems contain the world's largest biodiversity of vascular plants. Yet, our understanding of tropical functional diversity and its contribution to global diversity patterns is constrained by data availability. This discrepancy underscores an urgent need to bridge data gaps by incorporating comprehensive tropical root data into global datasets. Here, we provide a database of tropical root characteristics. This new database, TropiRoot 1.0, will be instrumental in evaluating an array of hypotheses pertaining to root functional ecology and plant biogeography, both within the tropics and relative to other global biomes. The data compilation was conducted by the TropiRoot Initiative, in partnership with the Fine‐Root Ecology Database (FRED) and the Global Root Trait (GRooT) database, Colorado State University (CSU) and the Smithsonian Tropical Research Institute (STRI). Literature search and data extraction were conducted between 2020 and 2024. Literature was identified using Web of Science, Scopus, and complemented using the expert knowledge of members of TropiRoot. To provide broad environmental and geographical distributions, literature searches included root characteristics (traits) across global change drivers, natural gradients, and from different continents. We adopted FRED standardized data columns and streamlined the format to enhance accessibility for data extraction across various user groups. This optimized framework resulted in a smaller, yet comprehensive datasheet. To make the database compatible with other global root trait initiatives, column identification was standardized following the codes provided by FRED. These efforts culminated in data extracted from 104 new sources, resulting in more than 8000 rows of data (either species or community data). Most of the data in TropiRoot 1.0 include root characteristics such as root biomass, morphology, root dynamics, mass fraction, architecture, anatomy, physiology, and root chemistry. This initiative represents a 30% increase in the currently available data for tropical roots in FRED. TropiRoot 1.0 contains root characteristics from 25 different countries, where seven are located in Asia, six in South America, five in Central America and the Caribbean, four in Africa, two in North America, and 1 in Oceania. Due to the volume of data, when ancillary data were available, including soil data, these data were either extracted and included in the database or its availability was recorded in an additional column. Multiple contributors checked the entries for outliers during the collation process to ensure data quality. For text‐based observations, we examined all cells to ensure that their content relates to their specific categories. For numerical observations, we ordered each numerical value from least to greatest and plotted the values, checking apparent outliers against the data in their respective sources and correcting or removing incorrect or impossible values. Some data (soil and aboveground) have different columns for the same variable presented in different units, including originally published units, but root characteristics data had units converted to match those reported in FRED. By filling a gap from global databases, TropiRoot 1.0 expands our knowledge of otherwise so far underrepresented regions and our ability to assess global trends. This advancement can be used to improve tropical forest representation in vegetation models. The data are freely available and should be cited when used.

Foraging location preferences reflect memory interference associated with spatial learning tasks in a food-caching bird - Lauren M. Benedict; Virginia K. Heinen; Joseph F. Welklin; Benjamin R. Sonnenberg; Lauren E. Whitenack; Eli S. Bridge; Vladimir V. Pravosudov (Animal Behaviour, 2025)

Phylosymbiosis and Elevated Cancer Risk in Genetically Depauperate Channel Island Foxes - Alexandra L. DeCandia; Jasmine Lu; Emily E. Hamblen; Lara J. Brenner; Julie L. King; Calypso N. Gagorik; Juliann T. Schamel; Stacy S. Baker; Francesca J. Ferrara; Melissa Booker; Andrew Bridges; Cesar Carrasco; et al. (Molecular Ecology, 2025)
Examination of the host‐associated microbiome in wildlife can provide critical insights into the eco‐evolutionary factors driving species diversification and response to disease. This is particularly relevant for isolated populations lacking genomic variation, a phenomenon that is increasingly common as human activities create habitat ‘islands’ for wildlife. Here, we characterised the gut and otic microbial communities of one such species: Channel Island foxes ( Urocyon littoralis ). The gut microbiome provided evidence of phylosymbiosis by reflecting the host phylogeny, geographic proximity, history of island colonisation and contemporary ecological differences, whereas the otic microbiome primarily reflected geography and disease. Santa Catalina Island foxes are uniquely predisposed to ceruminous gland tumours following infection with Otodectes cynotis ear mites, while San Clemente and San Nicolas Island foxes exhibit ear mite infections without evidence of tumours. Comparative analyses of otic microbiomes revealed that mite‐infected Santa Catalina and San Clemente Island foxes exhibited reduced bacterial diversity, skewed abundance towards the opportunistic pathogen Staphylococcus pseudintermedius and disrupted microbial community networks. However, Santa Catalina Island foxes uniquely harboured Fusobacterium and Prevotella bacteria as potential keystone taxa. These bacteria have previously been associated with colorectal cancer and may predispose Santa Catalina Island foxes to an elevated cancer risk. In contrast, mite‐infected San Nicolas Island foxes maintained high bacterial diversity and robust microbial community networks, suggesting that they harbour more resilient microbiomes. Considered together, our results highlight the diverse eco‐evolutionary factors influencing commensal microbial communities and their hosts and underscore how the microbiome can contribute to disease outcomes.

The high-resolution imaging science experiment (HiRISE) in the MRO extended science phases (2009–2023) - A.S. McEwen; S. Byrne; C. Hansen; I.J. Daubar; S. Sutton; C.M. Dundas; N. Bardabelias; N. Baugh; J. Bergstrom; R. Beyer; K.M. Block; V.J. Bray; et al. (Icarus, 2024)

Spatiotemporal variation in cognitive phenotype, social network position, and distribution of social associations in a food-caching bird - A. M. Pitera; V. K. Heinen; J. F. Welklin; C. L. Branch; B. R. Sonnenberg; L. M. Benedict; E. S. Bridge; V. V. Pravosudov (Behavioral Ecology and Sociobiology, 2024)

Nonequilibrium spherulitic magnetite in the Ryugu samples - Elena Dobrică; Hope A. Ishii; John P. Bradley; Kenta Ohtaki; Adrian J. Brearley; Takaaki Noguchi; Toru Matsumoto; Akira Miyake; Yohei Igami; Mitsutaka Haruta; Hikaru Saito; Satoshi Hata; et al. (Geochimica et Cosmochimica Acta, 2023)

Learning predictably changing spatial patterns across days in a food-caching bird - Lauren M. Benedict; Virginia K. Heinen; Benjamin R. Sonnenberg; Eli S. Bridge; Vladimir V. Pravosudov (Animal Behaviour, 2023)

Sexually concordant and dimorphic transcriptional responses to maternal trichloroethylene and/or N-acetyl cysteine exposure in Wistar rat placental tissue - Elana R. Elkin; Anthony L. Su; John F. Dou; Justin A. Colacino; Dave Bridges; Vasantha Padmanabhan; Sean M. Harris; Erica Boldenow; Rita Loch-Caruso; Kelly M. Bakulski (Toxicology, 2023)

Food-caching chickadees do not exhibit directional bias when learning a spatial task - Lauren M. Benedict; Virginia K. Heinen; Benjamin R. Sonnenberg; Angela M. Pitera; Eli S. Bridge; Vladimir V. Pravosudov (Behavioral Ecology and Sociobiology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effect of Activated Carbon in Thin Sand Caps Challenged with Ongoing PCB Inputs from Sediment Deposition: PCB Uptake in Clams (Mercenaria mercenaria) and Passive Samplers - Philip T. Gidley; Guilherme R. Lotufo; Alan J. Kennedy; Nicolas L. Melby; Allyson H. Wooley; Charles H. Laber; Robert M. Burgess; Carlos E. Ruiz; Todd S. Bridges (Archives of Environmental Contamination and Toxicology, 2022)

Consensus Guidelines for Advancing Coral Holobiont Genome and Specimen Voucher Deposition - Christian R. Voolstra; Kate M. Quigley; Sarah W. Davies; John Everett Parkinson; Raquel S. Peixoto; Manuel Aranda; Andrew C. Baker; Adam R. Barno; Daniel J. Barshis; Francesca Benzoni; Victor Bonito; David G. Bourne; et al. (Frontiers in Marine Science, 2021)
Coral research is being ushered into the genomic era. To fully capitalize on the potential discoveries from this genomic revolution, the rapidly increasing number of high-quality genomes requires effective pairing with rigorous taxonomic characterizations of specimens and the contextualization of their ecological relevance. However, to date there is no formal framework that genomicists, taxonomists, and coral scientists can collectively use to systematically acquire and link these data. Spurred by the recently announced “Coral symbiosis sensitivity to environmental change hub” under the “Aquatic Symbiosis Genomics Project” - a collaboration between the Wellcome Sanger Institute and the Gordon and Betty Moore Foundation to generate gold-standard genome sequences for coral animal hosts and their associated Symbiodiniaceae microalgae (among the sequencing of many other symbiotic aquatic species) - we outline consensus guidelines to reconcile different types of data. The metaorganism nature of the coral holobiont provides a particular challenge in this context and is a key factor to consider for developing a framework to consolidate genomic, taxonomic, and ecological (meta)data. Ideally, genomic data should be accompanied by taxonomic references, i.e., skeletal vouchers as formal morphological references for corals and strain specimens in the case of microalgal and bacterial symbionts (cultured isolates). However, exhaustive taxonomic characterization of all coral holobiont member species is currently not feasible simply because we do not have a comprehensive understanding of all the organisms that constitute the coral holobiont. Nevertheless, guidelines on minimal, recommended, and ideal-case descriptions for the major coral holobiont constituents (coral animal, Symbiodiniaceae microalgae, and prokaryotes) will undoubtedly help in future referencing and will facilitate comparative studies. We hope that the guidelines outlined here, which we will adhere to as part of the Aquatic Symbiosis Genomics Project sub-hub focused on coral symbioses, will be useful to a broader community and their implementation will facilitate cross- and meta-data comparisons and analyses.

Transcriptional profiling of the response to the trichloroethylene metabolite S-(1,2-dichlorovinyl)-l-cysteine revealed activation of the eIF2α/ATF4 integrated stress response in two in vitro placental models - Elana R. Elkin; Kelly M. Bakulski; Justin A. Colacino; Dave Bridges; Brian A. Kilburn; D. Randall Armant; Rita Loch-Caruso (Archives of Toxicology, 2021)

High diversity, abundance and distinct fish assemblages on submerged coral reef pinnacles compared to shallow emergent reefs - G. F. Galbraith; B. J. Cresswell; M. I. McCormick; T. C. Bridge; G. P. Jones (Coral Reefs, 2021)

Multi‐hypothesis comparison of Farquhar and Collatz photosynthesis models reveals the unexpected influence of empirical assumptions at leaf and global scales - Anthony P. Walker; Abbey L. Johnson; Alistair Rogers; Jeremiah Anderson; Robert A. Bridges; Rosie A. Fisher; Dan Lu; Daniel M. Ricciuto; Shawn P. Serbin; Ming Ye (Global Change Biology, 2021)
Mechanistic photosynthesis models are at the heart of terrestrial biosphere models (TBMs) simulating the daily, monthly, annual and decadal rhythms of carbon assimilation ( A ). These models are founded on robust mathematical hypotheses that describe how A responds to changes in light and atmospheric CO 2 concentration. Two predominant photosynthesis models are in common usage: Farquhar (FvCB) and Collatz (CBGB). However, a detailed quantitative comparison of these two models has never been undertaken. In this study, we unify the FvCB and CBGB models to a common parameter set and use novel multi‐hypothesis methods (that account for both hypothesis and parameter variability) for process‐level sensitivity analysis. These models represent three key biological processes: carboxylation, electron transport, triose phosphate use (TPU) and an additional model process: limiting‐rate selection. Each of the four processes comprises 1–3 alternative hypotheses giving 12 possible individual models with a total of 14 parameters. To broaden inference, TBM simulations were run and novel, high‐resolution photosynthesis measurements were made. We show that parameters associated with carboxylation are the most influential parameters but also reveal the surprising and marked dominance of the limiting‐rate selection process (accounting for 57% of the variation in A vs. 22% for carboxylation). The limiting‐rate selection assumption proposed by CBGB smooths the transition between limiting rates and always reduces A below the minimum of all potentially limiting rates, by up to 25%, effectively imposing a fourth limitation on A . Evaluation of the CBGB smoothing function in three TBMs demonstrated a reduction in global A by 4%–10%, equivalent to 50%–160% of current annual fossil fuel emissions. This analysis reveals a surprising and previously unquantified influence of a process that has been integral to many TBMs for decades, highlighting the value of multi‐hypothesis methods.

Coral reef annihilation, persistence and recovery at Earth’s youngest volcanic island - P. F. Smallhorn-West; J. B. Garvin; D. A. Slayback; T. M. DeCarlo; S. E. Gordon; S. H. Fitzgerald; T. Halafihi; G. P. Jones; T. C. L. Bridge (Coral Reefs, 2020)

Co-administration of Selenium with Inorganic Mercury Alters the Disposition of Mercuric Ions in Rats - Sarah E. Orr; Hannah S. George; Mary C. Barnes; Taylor N. Mathis; Lucy Joshee; Jennifer Barkin; Adam M. Kiefer; Caryn S. Seney; Christy C. Bridges (Biological Trace Element Research, 2020)

Correction to: Incongruence between life-history traits and conservation status in reef corals - Tom C. L. Bridge; Osmar J. Luiz; Chao-Yang Kuo; Kristin Precoda; Elizabeth M. P. Madin; Joshua S. Madin; Andrew H. Baird (Coral Reefs, 2020)

Incongruence between life-history traits and conservation status in reef corals - Tom C. L. Bridge; Osmar J. Luiz; Chao-Yang Kuo; Kristin Precoda; Elizabeth M. P. Madin; Joshua S. Madin; Andrew H. Baird (Coral Reefs, 2020)

Elevation-related differences in annual survival of adult food-caching mountain chickadees are consistent with natural selection on spatial cognition - L. M. Benedict; A. M. Pitera; C. L. Branch; D. Y. Kozlovsky; B. R. Sonnenberg; E. S. Bridge; V. V. Pravosudov (Behavioral Ecology and Sociobiology, 2020)

Expression and Characterization of a Bright Far-red Fluorescent Protein from the Pink-Pigmented Tissues of Porites lobata - Mary C. Bridges; Cheryl M. Woodley; Esther C. Peters; Lisa A. May; Sylvia B. Galloway (Marine Biotechnology, 2020)

Resolving the depth zonation paradox in reef‐building corals - T. Edward Roberts; Tom C. L. Bridge; M. Julian Caley; Joshua S. Madin; Andrew H. Baird (Ecology, 2019)
Changes in abundance across a natural environmental gradient provide important insights into a species’ realized ecological niche. In reef‐building corals, a species’ niche is often defined using its depth range. However, most reef‐building coral species occur over a broad depth range, a fact that is incompatible with the strong zonation found in coral assemblages across depth. We resolve this paradox by modeling the abundance distributions of 110 coral species across a 45 m depth gradient to show that most are in fact depth specialists and reveal that depth range alone is incapable of capturing a species’ depth use. We then highlight the significance of our results by demonstrating how depth range greatly overestimates the potential number of species with a refuge at depth from global warming. Our findings illustrate both the limitations of the simple metric of depth range and the ecological insights that can be gained by moving beyond it.

Smart is the new sexy: female mountain chickadees increase reproductive investment when mated to males with better spatial cognition - Carrie L. Branch; Angela M. Pitera; Dovid Y. Kozlovsky; Eli S. Bridge; Vladimir V. Pravosudov (Ecology Letters, 2019)
Understanding the evolution of inter and intraspecific variation in cognitive abilities is one of the main goals in cognitive ecology. In scatter‐caching species, spatial memory is critical for the recovery of food caches and overwinter survival, but its effects on reproduction are less clear. Better spatial cognition may improve pre‐breeding condition allowing for earlier reproduction. Alternatively, when mated to males with better spatial memory, females may be able to invest more in reproduction which may allow increased offspring survival and hence higher fitness. Using wild food‐caching mountain chickadees, we found that when environmental conditions were favourable for breeding, females mated to males with better spatial cognition laid larger clutches and fledged larger broods than females mated to males with worse cognitive performance. Our results support the hypothesis that females may increase their reproductive investment to gain indirect, genetic benefits when mated to high‐quality males with better spatial cognitive abilities.

Examining the Impact of a Web-Based Intervention to Promote Patient Activation in Chemotherapy-Induced Peripheral Neuropathy Assessment and Management - Robert Knoerl; Deborah Lee; James Yang; Celia Bridges; Grace Kanzawa-Lee; G. Lita Smith; Ellen M. Lavoie Smith (Journal of Cancer Education, 2018)

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

Edible wild plants growing in contaminated floodplains: implications for the issuance of tribal consumption advisories within the Grand Lake watershed of northeastern Oklahoma, USA - Ean M. Garvin; Cas F. Bridge; Meredith S. Garvin (Environmental Geochemistry and Health, 2018)

Contrasting patterns of changes in abundance following a bleaching event between juvenile and adult scleractinian corals - Mariana Álvarez-Noriega; Andrew H. Baird; Tom C. L. Bridge; Maria Dornelas; Luisa Fontoura; Oscar Pizarro; Kristin Precoda; Damaris Torres-Pulliza; Rachael M. Woods; Kyle Zawada; Joshua S. Madin (Coral Reefs, 2018)

Photo-induced toxicity in early life stage fiddler crab (Uca longisignalis) following exposure to Deepwater Horizon oil - Leigh M. Damare; Kristin N. Bridges; Matthew M. Alloy; Thomas E. Curran; Brianne K. Soulen; Heather P. Forth; Claire R. Lay; Jeffrey M. Morris; James A. Stoeckel; Aaron P. Roberts (Ecotoxicology, 2018)

Spiranthes igniorchis (Orchidaceae), a new and rare cryptic species from the south-central Florida subtropical grasslands - Matthew C. Pace; Steve L. Orzell; Edwin L. Bridges; Kenneth M. Cameron (Brittonia, 2017)

Contrasting post-settlement selection results in many-to-one mapping of high performance phenotypes in the Hawaiian waterfall-climbing goby Sicyopterus stimpsoni - Kristine N. Moody; Sandy M. Kawano; William C. Bridges; Richard W. Blob; Heiko L. Schoenfuss; Margaret B. Ptacek (Evolutionary Ecology, 2017)

Screening Level Assessment of Metal Concentrations in Streambed Sediments and Floodplain Soils within the Grand Lake Watershed in Northeastern Oklahoma, USA - Ean M. Garvin; Cas F. Bridge; Meredith S. Garvin (Archives of Environmental Contamination and Toxicology, 2017)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Factors influencing incidental representation of previously unknown conservation features in marine protected areas - Tom C.L. Bridge; Alana M. Grech; Robert L. Pressey (Conservation Biology, 2016)
Spatially explicit information on species distributions for conservation planning is invariably incomplete; therefore, the use of surrogates is required to represent broad‐scale patterns of biodiversity. Despite significant interest in the effectiveness of surrogates for predicting spatial distributions of biodiversity, few researchers have explored questions involving the ability of surrogates to incidentally represent unknown features of conservation interest. We used the Great Barrier Reef marine reserve network to examine factors affecting incidental representation of conservation features that were unknown at the time the reserve network was established. We used spatially explicit information on the distribution of 39 seabed habitats and biological assemblages and the conservation planning software Marxan to examine how incidental representation was affected by the spatial characteristics of the features; the conservation objectives (the minimum proportion of each feature included in no‐take areas); the spatial configuration of no‐take areas; and the opportunity cost of conservation. Cost was closely and inversely correlated to incidental representation. However, incidental representation was achieved, even in a region with only coarse‐scale environmental data, by adopting a precautionary approach that explicitly considered the potential for unknown features. Our results indicate that incidental representation is enhanced by partitioning selection units along biophysical gradients to account for unknown within‐feature variability and ensuring that no‐take areas are well distributed throughout the region; by setting high conservation objectives that (in this case >33%) maximize the chances of capturing unknown features incidentally; and by carefully considering the designation of cost to planning units when using decision‐support tools for reserve design. The lessons learned from incidental representation in the Great Barrier Reef have implications for conservation planning in other regions, particularly those that lack detailed environmental and ecological data.

Population development within the coffee wilt pathogen Gibberella xylarioides reflects host-related divergence - A. G. Buddie; J. Crozier; M. A. Rutherford; J. Flood; P. D. Bridge (European Journal of Plant Pathology, 2015)

Benthic community composition on submerged reefs in the central Great Barrier Reef - T. E. Roberts; J. M. Moloney; H. P. A. Sweatman; T. C. L. Bridge (Coral Reefs, 2015)

Population dynamics of redbay (Persea borbonia) after laurel wilt disease: an assessment based on forest inventory and analysis data - Timothy M. Shearman; G. Geoff Wang; William C. Bridges (Biological Invasions, 2015)

Depressive symptoms in chronic hepatitis C are associated with plasma apolipoprotein E deficiency - David A. Sheridan; S. H. Bridge; M. M. E. Crossey; D. J. Felmlee; H. C. Thomas; R. D. G. Neely; S. D. Taylor-Robinson; M. F. Bassendine (Metabolic Brain Disease, 2014)

Usefulness and uses of climate forecasts for agricultural extension in South Carolina, USA - Scott R. Templeton; M. Shane Perkins; Heather Dinon Aldridge; William C. Bridges; Bridget Robinson Lassiter (Regional Environmental Change, 2014)

Differences in locomotor behavior correspond to different patterns of morphological selection in two species of waterfall-climbing gobiid fishes - Sandy M. Kawano; William C. Bridges; Heiko L. Schoenfuss; Takashi Maie; Richard W. Blob (Evolutionary Ecology, 2013)

Lipids and HCV - M. F. Bassendine; D. A. Sheridan; S. H. Bridge; D. J. Felmlee; R. D. G. Neely (Seminars in Immunopathology, 2013)

Diversity of Scleractinia and Octocorallia in the mesophotic zone of the Great Barrier Reef, Australia - T. C. L. Bridge; K. E. Fabricius; P. Bongaerts; C. C. Wallace; P. R. Muir; T. J. Done; J. M. Webster (Coral Reefs, 2012)

Comparison of the Effects of Antimicrobial Agents from Three Different Classes on Metabolism of Isoflavonoids by Colonic Microflora Using Etest Strips - John B. Sutherland; Brad M. Bridges; Thomas M. Heinze; Michael R. Adams; Patrick J. Delio; Charlotte Hotchkiss; Fatemeh Rafii (Current Microbiology, 2012)

Topography, substratum and benthic macrofaunal relationships on a tropical mesophotic shelf margin, central Great Barrier Reef, Australia - T. C. L. Bridge; T. J. Done; R. J. Beaman; A. Friedman; S. B. Williams; O. Pizarro; J. M. Webster (Coral Reefs, 2011)

A histological investigation of the occurrence of non‐reproductive female bluefin tuna Thunnus thynnus in the Mediterranean Sea - R. Zupa; A. Corriero; M. Deflorio; N. Santamaria; D. Spedicato; C. Marano; M. Losurdo; C. R. Bridges; G. De Metrio (Journal of Fish Biology, 2009)
The presence of non‐reproductive Atlantic bluefin tuna Thunnus thynnus females in the Mediterranean Sea was investigated through histological analysis of the gonads. Three hundred and twenty‐six ovary samples were collected from adults captured at different locations in the Mediterranean Sea during the reproductive seasons between 1998 and 2008. Only three specimens were considered to be in a non‐reproductive state: two of them were in a reabsorbing state showing ovaries with early vitellogenic oocytes and extensive α and β atresia of vitellogenic follicles; the third showed gonads with perinucleolar oocytes and was considered to be in a resting state. The low occurrence of non‐reproductive individuals found in this study makes it unlikely that non‐reproductive individuals aggregate with reproductive ones during their migration towards spawning grounds. Further research is suggested in order to investigate the potential presence of non‐reproductive individuals on non‐spawning grounds during the reproductive season.

An association between the Antarctic mite Alaskozetes antarcticus and an entomophthoralean fungus of the genus Neozygites - P. D. Bridge; M. R. Worland (Experimental and Applied Acarology, 2008)

Effects of hypoxia on the energy status and nitrogen metabolism of African lungfish during aestivation in a mucus cocoon - A. M. Loong; S. F. Ang; W. P. Wong; H. O. Pörtner; C. Bock; R. Wittig; C. R. Bridges; S. F. Chew; Y. K. Ip (Journal of Comparative Physiology B, 2008)

Domain II Hairpin Structure in ITS1 Sequences as an Aid in Differentiating Recently Evolved Animal and Plant Pathogenic Fungi - P. D. Bridge; T. Schlitt; P. F. Cannon; A. G. Buddie; M. Baker; A. M. Borman (Mycopathologia, 2008)

Germ cell proliferation and apoptosis during different phases of swordfish ( Xiphias gladius L.) spermatogenetic cycle - A. Corriero; S. Desantis; C. R. Bridges; D. E. Kime; P. Megalofonou; N. Santamaria; F. Cirillo; G. Ventriglia; A. Di Summa; M. Deflorio; F. Campobasso; G. De Metrio (Journal of Fish Biology, 2007)
Seasonal changes of testicular activity of the swordfish Xiphias gladius and correlations of plasma levels of testosterone (T) and 11‐ketotestosterone (11‐KT) with proliferation and apoptosis of germ cells, determined, respectively, with monoclonal antibodies against proliferating cell nuclear antigen and terminal deoxynucleotidyl transferase‐mediated d’UTP nick end labelling, are described. Three phases of the reproductive cycle were found: active spermatogenic (May), spawning (June to July) and spent (August to September) stages. Germ cell proliferating activity was highest in May, decreased during June to July and remained stable during August to September. Apoptotic germ cells, primary spermatocytes and spermatogonia, were present in all the specimens analysed and were more abundant in May. The levels of 11‐KT in plasma were always higher than T and were highest in May, in concomitance with the maximum proliferation and apoptosis rate of germ cells.

Partnering in Oncogenetic Research – The INHERIT BRCAs Experience: Opportunities and Challenges - Denise Avard; Peter Bridge; Lucie M. Bucci; Jocelyne Chiquette; Michel Dorval; Francine Durocher; Doug Easton; Béatrice Godard; David Goldgar; Bartha Maria Knoppers; Rachel Laframboise; Bernard Lespérance; et al. (Familial Cancer, 2006)

Toxicological comments to the discussion about REACH - Helmut Greim; Michael Arand; Herman Autrup; Hermann M. Bolt; James Bridges; Erik Dybing; Rémi Glomot; Vito Foa; Rolf Schulte-Hermann (Archives of Toxicology, 2006)

Assessing Contaminant Sensitivity of Endangered and Threatened Aquatic Species: Part I. Acute Toxicity of Five Chemicals - F. J. Dwyer; F. L. Mayer; L. C. Sappington; D. R. Buckler; C. M. Bridges; I. E. Greer; D. K. Hardesty; C. E. Henke; C. G. Ingersoll; J. L. Kunz; D. W. Whites; T. Augspurger; et al. (Archives of Environmental Contamination and Toxicology, 2005)

Variations on a theme? Polyp and medusa development in Podocoryna carnea - Diane M. Bridge; Chi T. Ha; Audra Nemir; Andrea Renden; Mary M. Rorick; Amie Shaffer; Danielle M. Underkoffler; Andrea E. Wills; Daniel E. Martínez (Hydrobiologia, 2004)

Revealing gene transcription and translation initiation patterns in archaea, using an interactive clustering model - Xiu-Feng Wan; Susan M. Bridges; John A. Boyle (Extremophiles, 2004)

Influence of environmental temperature on exercise-induced inspiratory muscle fatigue - Lee M. Romer; Matthew W. Bridge; Alison K. McConnell; David A. Jones (European Journal of Applied Physiology, 2004)

First report of an entomophthoralean fungus on an arthropod host in Antarctica - P. D. Bridge; M. R. Worland (Polar Biology, 2004)

Histological investigation on the ovarian cycle of the bluefin tuna in the western and central Mediterranean - A. Corriero; S. Desantis; M. Deflorio; F. Acone; C. R. Bridges; J. M. De la Serna; P. Megalofonou; G. De Metrio (Journal of Fish Biology, 2003)
The histological analysis of eastern Atlantic bluefin tuna Thunnus thynnus ovaries caught from February to September 1999–2000, made it possible to distinguish the presence of seven oocyte developmental stages and allowed the characterization of six time‐dependent ovary maturity stages. The ovaries of mature (fork length, L F ≥ 110 cm) bluefin tuna were non‐active from August (spent period) to March (quiescent period) when they contained only perinucleolar‐stage oocytes. Ovary development started in April to early May (recrudescent period) with the appearance of oocytes at the lipid stage. Vitellogenesis appeared in mid‐May (ripening period) and post‐vitellogenesis occurred in late May to mid‐June (pre‐spawning period). In late June to early July, hydrated oocytes, a sign of imminent spawning, were found only in specimens caught in Balearic waters. Females ranging between 100 and 110 cm L F , captured during the recrudescent and ripening periods, had the largest oocytes at the lipid stage, most of which were degenerating. An extensive vitellogenic atresia was observed in the ovaries of five females caught during the spawning period in non‐spawning areas.

Comparative Contaminant Toxicity: Are Amphibian Larvae More Sensitive than Fish? - C. M. Bridges; F. J. Dwyer; D. K. Hardesty; D. W. Whites (Bulletin of Environmental Contamination and Toxicology, 2002)

Growth and development of larval green frogs (Rana clamitans) exposed to multiple doses of an insecticide - Michelle D. Boone; Christine M. Bridges; Betsie B. Rothermel (Oecologia, 2001)

Quantifying the 5-HT 1A agonist action of buspirone in man - Bridge M.; Marvin G.; Thompson C.; Sharma A.; Jones D.; Kendall M. (Psychopharmacology, 2001)

Variation in Pesticide Tolerance of Tadpoles among and within Species of Ranidae and Patterns of Amphibian Decline - Christine M. Bridges; Raymond D. Semlitsch (Conservation Biology, 2000)
There is significant variation among and within amphibian species with respect to reports of population decline; declining species are often found in environments that are physiograpically similar to environments where the same species is thriving. Because variability exists among organisms in their sensitivity to environmental stressors, it is important to determine the degree of this variation when undertaking conservation efforts. We conducted both lethal (time‐to‐death) and sublethal (activity change) assays to determine the degree of variation in the sensitivity of tadpoles to a pesticide, carbaryl, at three hierarchical levels: among ranid species, among several populations of a single ranid species ( Rana sphenocephala ), and within populations of R. sphenocephala . We observed significant variation in time to death among the nine ranid species and among the 10 R. sphenocephala populations we tested. Four out of eight R. sphenocephala populations exhibited significantly different times to death among families. The magnitude of the activity change in response to exposure to sublethal carbaryl levels was significantly different among species and within R. sphenocephala populations. Chemical contamination, at lethal or sublethal levels, can alter natural regulatory processes such as juvenile recruitment in amphibian populations and should be considered a contributing cause of declines in amphibian populations.

Long-Term Effects of Pesticide Exposure at Various Life Stages of the Southern Leopard Frog ( Rana sphenocephala ) - C. M. Bridges (Archives of Environmental Contamination and Toxicology, 2000)

Predator-prey interactions between two amphibian species: effects of insecticide exposure - Christine M. Bridges (Aquatic Ecology, 1999)

Comparison of rRNA genotype frequencies ofParmelia sulcata from long established and recolonizing sites following sulphur dioxide amelioration - A. Crespo; P. D. Bridge; D. L. Hawksworth; M. Grube; O. F. Cubero (Plant Systematics and Evolution, 1999)

Regulation of MMP-9 (92 kDa type IV collagenase/gelatinase B) expression in stromal cells of human giant cell tumor of bone - Velidi H. Rao; Rakesh K. Singh; Julia A. Bridge; James R. Neff; G. Bradley Schaefer; Duane C. Delimont; Christopher M. Dunn; Warren G Sanger; Bruce A. Buehler; Raymond Sawaya; Garth L. Nicolson; Jasti S. Rao (Clinical & Experimental Metastasis, 1997)

Molecular characterization of isolates of Metarhizium from locusts and grasshoppers - P. D. Bridge; C. Prior; J. Sagbohan; C. J. Lomer; M. Carey; A. Buddie (Biodiversity and Conservation, 1997)

Factors influencing peroxisome proliferation in cultured rat hepatocytes - Angela M. Mitchell; James W. Bridges; Clifford R. Elcombe (Archives of Toxicology, 1984)

A new species ofSchwanniomyces: Schwanniomyces alluvius - H. J. Phaff; M. W. Miller; Wm. Bridge Cooke (Antonie van Leeuwenhoek, 1960)